Pengaruh Prinsip-Prinsip Good Corporate Governance, Motivasi, dan Budaya Organisasi Terhadap Kinerja Karyawan - Putri, Ni Kadek Desy Yasinta; Putra, I Made Pande Dwiana (E-Jurnal Akuntansi; Vol 21 No 2 (2017), 2017)
Performance is a description of the level of achievement of the implementation of an activity or policy in realizing the goals, vision and mission of the organization contained in strategic planning of an organization. In an increasingly competitive world of banking, current performance measurement is not only done financially, but non-financial conditions can also show the performance of the company. The success of an organization is strongly influenced by the performance of its employees. Badung regency with the largest number of BPR in Bali Province also demanded BPR to improve its performance, both organizational performance and employee performance in order to maintain its organizational survival in the middle of competition between BPR and with Commercial Bank. Many factors can affect employee performance, some of which are Good Corporate Governance, motivation and organizational culture. This study aims to determine the influence of Good Corporate Governance, motivation and organizational culture on employee performance. This research was conducted on 52 BPR spread in Badung regency. The sample used in this study amounted to 132 respondents by using purposive sampling method. Data analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that the principles of good corporate governance namely accountability and independence have a positive effect on employee performance, while transparency, responsibility and fairness does not affect employee performance. Variables motivation and organizational culture have a positive effect on employee performance.